Sap Flow Disruption in Grapevine Is the Early Signal Predicting the Structural, Functional, and Genetic Responses to Esca Disease - Ouadi, Loris; Bruez, Emilie; Bastien, Sylvie; Yacoub, Amira; Coppin, Cindy; Guérin-Dubrana, Lucia; Fontaine, Florence; Domec, Jean-Christophe; Rey, Patrice (Frontiers in Plant Science, 2021)
Fungal species involved in Esca cause the formation of grapevine wood necroses. It results in the deterioration of vascular network transport capacity and the disturbance of the physiological processes leading to gradual or sudden grapevine death. Herein, for two consecutive growing seasons a detailed analysis of the structural (wood necrosis and leaf discoloration) and physiological parameters related to the water use of healthy and Esca-symptomatic grapevines was conducted. Measurements were carried out on 17 years old grapevines that expressed, or not, Esca-leaf symptoms in a vineyard of the Bordeaux region (France). Whole-plant transpiration was recorded continuously from pre-veraison to harvest using non-invasive sap flow sensors. Whole-plant transpiration was systematically about 40% to 50% lower in Esca-diseased grapevines compared to controls, and this difference can be observed around two weeks before the first Esca-foliar symptoms appeared in the vineyard. Unlike grapevine sap flow disruption, structural (e.g. leaf discolorations), functional (e.g. stomatal conductance, photosynthetic activity, phenolic compounds) and genetic (e.g. expression of leaf targeted genes) plant responses were only significantly impacted by Esca at the onset and during leaf symptoms development. We conclude that sap flow dynamic, which was related to a high level of white-rot necrosis provides a useful tool to predict plant disorders due to Esca-grapevine disease.